ChemInform Abstract: Iron‐Catalyzed Direct Synthesis of Densely Substituted Benzofurans and Naphthopyrans from Phenolic Compounds and Propargylic Alcohols. Issue 30 (4th July 2013) - Yuan, Feng‐Quan; Han, Fu‐She
Abstract The outcome of the title reaction is controlled by the structural nature of the propargyl alcohol.